Using a policy learning lens to understand health financing policy outcomes: the case of translating strategic health purchasing into policy and practice in Burkina Faso - Kiendrébéogo, Joël; De Allegri, Manuela; Damme, Wim Van; Meessen, Bruno (BMJ global health, 2024)
Introduction Achieving universal health coverage (UHC) through an effective health financing system is a challenge for many low-income countries. Learning is key to success due to many uncertainties and unknowns. Using the case of translating strategic health purchasing into policy and practice in Burkina Faso, our study seeks to understand how policy learning can shape policy processes and outcomes.Methods We used a qualitative case study design and Dunlop and Radaelli’s conceptualisation of policy learning to identify which modes of learning did or did not occur, what helped or hindered them and the resulting policy outcomes. Dunlop and Radaelli frame policy learning as epistemic, reflexive, negotiative or hierarchical. We collected data through documentary review and in-depth individual interviews with 21 key informants. We analysed the data manually using pattern-matching techniques.Results The introduction of strategic health purchasing in Burkina Faso was initially seen as an opportunity to reduce the fragmentation of the health financing system by coupling a performance-based financing scheme and a user fee exemption policy. However, this has faltered, and our findings suggest that an inability to harness all modes of learning has led to blockages. Indeed, while reflective learning was present, epistemic, hierarchical and learning through bargaining were absent, preventing national policy actors from defending their own policy or scheme from reaching compromises. But thanks to facilitating processes led by a well-resourced organisation and contextual elements that encouraged the emergence of more pluralistic modes of learning, some progress was achieved in operationalising strategic health purchasing.Conclusions Some modes of learning seem to be overlooked in countries’ efforts to achieve UHC. Facilitation techniques and initiatives that encourage the use of all modes of learning, while supporting countries to take full ownership and responsibility for consolidating their own learning health systems, should be promoted.